Morphological and ultrastructural characteristics of the tongue of wild boar - Reginato, Gabriela de Souza [UNESP]; Barbosa, Gabriela Klein [UNESP]; Ferreira, Amanda Olivotti; Vasconcelos, Bruno Gomes; Rici, Rose Eli Grassi; Watanabe, Ii-Sei; Ciena, Adriano Polican [UNESP] (PAGEPress Publications, 2020)
The present study aimed to describe the structural and ultrastructural morphological characteristics of the lingual epithelium and the connective tissue cores (CTCs) of wild boar (Sus scrofa). The tongues were processed for light microscopy, scanning electron microscopy, and transmission electron microscopy. In this study, we revealed the filiform, fungiform, foliate, and vallate papillae. The filiform papilla is elongated with a conical shape and its CTC has a conical shape; the fungiform papilla is rounded with a dome-shape and its CTC is flow-er bud; the foliate papilla is formed by four pairs of epithelial folds and irregular grooves, and its CTC is thin with adjacent conjunctive projections, and taste buds and serous glands in the epithelial layer have been evi-denced; and the vallate papilla is oval surrounded by a groove with increases of epithelium surface, and theCTC is formed by numerous connective projections linedby a deep u segroove. Also noted were serous gland and taste buds on the medial wall of the vallate papilla. The epithelium has the keratinized,onlygranular, spinous, basal, and lamina propria layers. In conclusion, we found new descriptions and shapes of the CTCs of the lingual papillae. In addition, we demonstrated the epithelium structural characteristics, the nuclear distribution between the epithelial layers, and the ultrastructural aspects of the dorsal epithelium of the tongue.
Keywords: Epithelium; Lingual papillae; Morphology; Tongue; Wild boar